Treatment compliance and self care practices among type 2 diabetes mellitus patients at Kota Samarahan health Clinic, Sarawak 2009 - Nur Fatihah Oh, Abdulah (Universiti Malaysia Sarawak (UNIMAS), 2009)
Treatment compliance and self care practices are important factors in the management of diabetes. It can improve glycaemic control and prevent or delay diabetes related complications which cause reduction in quality of life and disease burden in term oftreatment cost A primary health care clinic was chosen for this study. The objectives ofthis study were to determine the status of compliance and self care practices and its relation to fasting blood sugar among Type -2 Diabetes Mellitus patients) A cross sectional study was done by using guided self report questionnaire and involving 163 respondents aged above 30 years old. The questionnaire includes socio demographic status, fasting blood sugar result, risk factors, compliance towards treatment and follow up visit as well as self care practices. SPSS version 14 was used to analyse the variables with test of significance at p < 0.05. Among the respondents the good compliance was 93.3%. Based on fasting blood glucose 49.1 % were good control (FBS = 4.4 -6.lmmollL) and 50.9% were poor control (FBS> 6.1mmol/L). There was a significant association between compliance and fasting blood glucose (p< 0.05). There was significant association between level of income and types of occupation with compliance (p< 0.05). The good compliance was observed among female as compared to male with test of significance p<0.05. However there was no association between self care practices and fasting blood glucose. As a conclusion treatment compliance influence fasting blood sugar and factors like income and occupation do influence compliance among these respondents.